Semio-Mitologi Roland Barthes Terhadap Makna Al-Magá¸ub dan Ad-á¸Œallin Q.S Al-Fatihah: 7 - Muhammad Irfani; Almeyda Farabi Z.R; Muhammad Sayyid An Nabiil; Mohammad Zakaria Drajat Dahlan; imam muhajir putra (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Understanding vocabulary is one of the main things in understanding the messages conveyed by the Qur’an as a guideline for life. Symbols or signs are concrete elements that help the mufasir reveal the diversity of meanings and messages in the Qur’an. The purpose of this research is to discover the mythology of the meaning of al-magḍūb and al-ḍāllīn in Q.S al-Fatiha [1]:7 and trace the message of its contents. This study uses Roland Barthes’ semiotic theory, namely the linguistic and mythical systems, to reveal the meanings of al-magḍūb and ad-ḍāllīn. To achieve this goal, this study uses a qualitative method and concludes that, in the linguistic context, the words al-magḍūb and ad-ḍāllīn refer to groups of Jews and Christians, respectively. In the mythical context, al-magḍūb is described as envious, disobedient, and prioritizing personal interests; ad-ḍāllīn is described as careless in his actions because he lacks a basis in knowledge and is easily discouraged from doing something. These two things are despicable traits that are dominated by the interests of lust in all their actions.